Import dependence of the European organic market and the role of Ukrainian exports - Nifatova, Olena; Danko, Yuriy; Petrychuk, Svitlana; Baležentis, Tomas; Štreimikienė, Dalia (Technological and Economic Development of Economy, 2024)
The European market for organic products has been expanding, with a persistent difference between the growth rates of organic retail trade (actual demand for organic products) and the growth rates of organic agricultural land areas (potential supply of organic products). This makes the European Union (EU) dependent on global imports. This research focuses on the import of organic products from Ukraine. To understand the underlying factors of the EU-27 countries’ import dependence on Ukrainian exports, this article proposes the following: 1) an analysis of Ukraine’s contribution to the total import volume to EU-27 countries by categories of organic products that have the most significant share in overall imports from Ukraine (these categories include: cereals, other than wheat and rice; soybeans; wheat; oilseeds, other than soybeans); 2) a study of the general trends of the European organic market’s import dependence on imports from Ukraine by the categories with the highest contribution; 3) clustering of the EU-27 countries based on organic market indicators; 4) an analysis of the European organic market using Ukrainian imports as an example. Ukrainian imports do not threaten the domestic European market; instead, countries with the highest level of dependence can use Ukrainian organic raw materials for processing and further re-export.